APPLICATION OF AI WRITING ASSISTANT SOFTWARE IN EFL WRITING IN CHINA: A REVIEW - Li Qiu; Suyansah Swanto; Noraini Said; Wardatul Akmam Din, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Technological innovations and the need for mastery of the English language in China have contributed to the introduction of Artificial Intelligence (henceforth AI) in teaching and learning the English language. The rationality behind this article is the need to understand and optimize the acquisition and the teaching of English writing skill among China EFL students and teachers. The purpose of this review is two fold. First, author wanted to explore the features, benefits and challenges of AI utilized in teaching and learning English language. Next, this review also sought to explore the strength and limitations of AI-based writing assistant software. To do this, as systematic review was conducted concerning the application and research of AI in language education have been reviewed to investigate the varying contributions that AI has had in the teaching and learning of English language writing. Using Scopus database, a total of 84 peer-reviewed papers were identified and 21 were analyzed. It further analyses sites such as Pigai.org, Iwrite, and other valuable software to assist in determining the required results. An in-depth analysis and evaluation of the use of AI in the teaching of English writing skill seems to suggest that the use of automated writing evaluation (henceforth AWE) or automated essay scoring (henceforth AES) has greatly facilitated the tasks of English writing skill acquisition, the identification of the areas of improvement that need to be focused on in the process of student’s writing, as well as issues and challenges related to the use of online resources at colleges and universities in China to enable the teaching and learning of the English language, particularly writing skill to be executed more effectively.